2017
DOI: 10.1371/journal.pone.0173910
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurement of interaction forces between bovine serum albumin and poly(ethylene oxide) in water and electrolyte solutions

Abstract: The net interaction between a probe tip coated with bovine serum albumin (BSA) protein and a flat substrate coated with poly(ethylene oxide) (PEO) polymer was measured directly on approach in water and electrolyte solutions using AFM. The approach force curve between the two surfaces was monotonically repulsive in water and in electrolyte solutions. At pH ~5, slightly above the isoelectric point (pI) of BSA, and at large distances, the force was dominated by electrostatic repulsion between the oxygen atoms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…The 10% PPAA/PLGA blend MPs demonstrated a modestly faster and higher cumulative release, where the rate of release was directly proportional to the PPAA content. Previous work by Acuña et al demonstrated electrostatic repulsion between oxygen atoms in ether groups of poly(ethylene oxide) and bovine serum albumin a weak polyelectrolyte and modestly negatively charged protein. Work by Weijers et al demonstrating a stronger negative charge of OVA plus the increased polarity of carboxyl groups, compared to ether, lead us to believe a strong repulsion between the two is possible.…”
Section: Discussionmentioning
confidence: 99%
“…The 10% PPAA/PLGA blend MPs demonstrated a modestly faster and higher cumulative release, where the rate of release was directly proportional to the PPAA content. Previous work by Acuña et al demonstrated electrostatic repulsion between oxygen atoms in ether groups of poly(ethylene oxide) and bovine serum albumin a weak polyelectrolyte and modestly negatively charged protein. Work by Weijers et al demonstrating a stronger negative charge of OVA plus the increased polarity of carboxyl groups, compared to ether, lead us to believe a strong repulsion between the two is possible.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work have found the BSA deposit on glass slides to be uniform and monodisperse. 54 Contact angle was measured using a fully automated optical tensiometer (Theta ATA Scientific) via a sessile drop method over the coated glass slide. Contact angle was recorded for the first 60 s during which the structure of the droplet was maintained, analysed using a Young–Laplace curve-fitting model and averaged over 4 drops.…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, methods designed for identifying “hard” coronas of irreversibly adsorbed proteins may easily disturb “soft” coronas of weakly adsorbed proteins in dynamic equilibrium. In another case, direct mechanical force measurements between surface immobilized PEG and proteins have shown attractive interactions for some conditions (e.g., molecular weight, solvent quality); , however, such measurements employ relatively strong compressive loads that may perturb interactions compared to what is encountered in kT -scale diffusive collisions and equilibrium binding events. Considering varied and sometimes conflicting results from current methods, a better understanding of PEG–protein interactions might be achieved from more direct, sensitive artifact-free measurements with straightforward interpretation.…”
Section: Introductionmentioning
confidence: 99%